Transcriptome Analysis to Study the Molecular Response in the Gill and Hepatopancreas Tissues of Macrobrachium nipponense to Salinity Acclimation - Xue, Cheng; Xu, Kang; Jin, Yiting; Bian, Chao; Sun, Shengming (Frontiers in Physiology, 2022)
Macrobrachium nipponense is an economically important prawn species and common in Chinese inland capture fisheries. During aquaculture, M. nipponense can survive under freshwater and low salinity conditions. The molecular mechanism underlying the response to salinity acclimation remains unclear in this species; thus, in this study, we used the Illumina RNA sequencing platform for transcriptome analyses of the gill and hepatopancreas tissues of M. nipponense exposed to salinity stress [0.4‰ (S0, control group), 6‰ (S6, low salinity group), and 12‰ (S12, high salinity group)]. Differentially expressed genes were identified, and several important salinity adaptation-related terms and signaling pathways were found to be enriched, such as “ion transport,” “oxidative phosphorylation,” and “glycometabolism.” Quantitative real-time PCR demonstrated the participation of 12 key genes in osmotic pressure regulation in M. nipponense under acute salinity stress. Further, the role of carbonic anhydrase in response to salinity acclimation was investigated by subjecting the gill tissues of M. nipponense to in situ hybridization. Collectively, the results reported herein enhance our understanding of the mechanisms via which M. nipponense adapts to changes in salinity.